Linking smallholders to the new agricultural economy: The case of the plataformas de concertación in Ecuador - Cavatassi, Ramina; González-Flores, Mario; Winters, Paul; Andrade-Piedra, Jorge; Espinosa, Patricio; Thiele, Graham (International Food Policy Research Institute, 2016)
The authors of Chapter 12 (Cavatassi et al.) performed an ex-post evaluation using econometric techniques common in impact evaluations. They assessed whether participation in Ecuador’s Plataformas program, which establishes alliances between small-scale farmers and a range of agricultural support-service providers, had any effect on income. The chapter finds that the program had a positive impact on yields, prices, and gross margins. The authors conducted baseline household and community surveys in two Ecuadorean provinces and then identified treatment communities. Using data from the most recent census, they constructed a counterfactual control group with similar geographical, agroecological, and sociodemographic characteristics to the treatment communities. They then used PSM to identify which control communities were most similar to each treatment community. In addition to creating control communities, they also factored in households in treatment communities that did not participate in the program. The PSM procedure allowed the authors to select a control community that was very similar to each treatment community in all observable aspects except for the treatment status, thus providing a proper counterfactual for each treatment community.